Challenging the curve: can ChatGPT-generated MCQs reduce grade inflation in pharmacy education - Almaghaslah, Dalia (Frontiers in Pharmacology, 2025)
IntroductionGrade inflation in higher education poses challenges to maintaining academic standards, particularly in pharmacy education, where assessing student competency is crucial. This study investigates the impact of AI-generated multiple-choice questions (MCQs) on exam difficulty and reliability in a pharmacy management course at a Saudi university.MethodsA quasi-experimental design compared the 2024 midterm exam, featuring ChatGPT-generated MCQs, with the 2023 exam that utilized human-generated questions. Both exams covered identical topics. Exam reliability was assessed using the Kuder-Richardson Formula 20 (KR-20), while difficulty and discrimination indices were analyzed. Statistical tests, including t-tests and chi-square tests, were conducted to compare performance metrics.ResultsThe 2024 exam demonstrated higher reliability (KR-20 = 0.83) compared to the 2023 exam (KR-20 = 0.78). The 2024 exam included a greater proportion of moderate questions (30%) and one difficult question (3.3%), whereas the 2023 exam had 93.3% easy questions. The mean student score was significantly lower in 2024 (17.75 vs. 21.53, p < 0.001), and the discrimination index improved (0.35 vs. 0.25, p = 0.007), indicating enhanced differentiation between students.DiscussionThe findings suggest that AI-generated MCQs contribute to improved exam rigor and a potential reduction in grade inflation. However, careful review of AI-generated content remains essential to ensure alignment with course objectives and accuracy.ConclusionAI tools like ChatGPT offer promising opportunities to enhance assessment integrity and support fairer evaluations in pharmacy education.